Cross-species single-cell landscapes identify the pathogenic gene characteristics of inherited retinal diseases - Hu, Hualei; Liu, Fei; Gao, Pan; Huang, Yuwen; Jia, Danna; Reilly, Jamas; Chen, Xiang; Han, Yunqiao; Sun, Kui; Luo, Jiong; Li, Pei; Zhang, Zuxiao; et al. (Frontiers in Genetics, 2024)
Introduction: Inherited Retinal diseases (IRDs) affect ~4.5 million people worldwide. Elusive pathogenic variants in over 280 genes are associated with one or more clinical forms of IRDs. It's necessary to understand the complex interaction among retinal cell types and pathogenic genes by constructing a regulatory network. Here, we try to establish a panoramic expression view of the cooperative work in retinal cells to understand the clinical manifestations and pathogenic bases underlying IRDs.Methods: Single cell RNA sequencing (scRNAseq) data from the retinas from 35 retina samples of three species (human, mouse and zebrafish) including 259,087 cells were adopted to a comparative analysis across species. Bioinformatic tools were used to conduct Weighted Gene Co-expression Network Analysis, Single-cell regulatory network analysis, Cell-cell communication analysis, and trajectory inference analysis.The cross-species comparison revealed shared or species-specific gene expression patterns at single-cell resolution, such as the stathmin family genes, which were highly expressed specifically in zebrafish Müller glias (MGs). Thirteen gene modules were identified, of which nine were associated with retinal cell types, and Gene Ontology (GO) enrichment of module genes is consistent with cell-specific highly expressed genes. Many IRDs genes were identified as hub-genes and cell-specific regulons. Most IRDs, especially the RP genes, were enriched in rodspecific regulons. Integrated expression and transcription regulatory network, such as CSNB genes GRK1, PDE6B, TRPM1, showed cell-specific expression and transcription characteristics in either rods or bipolar cells. IRDs genes showed evolutionary conservation (GNAT2, PDE6G, SAG) and divergence (GNAT2, MT-ND4, PDE6A) along the trajectory of photoreceptors among species. In particular, the Leber Congenital Amaurosis (LCA) gene OTX2 showed high expression at the beginning of the trajectory of both photoreceptors and BCs.We have identified molecular pathways and cell types tightly connected with IRDs, bridging the gap between gene expression, genetic and pathogenesis. The IRDs genes enriched in cell-specific modules and regulons suggest that these diseases share common etiological bases. Overall, mining of interspecies-transcriptome data reveals conserved transcriptomic features of retinas across species, and promising applications in both normal retina anatomy and retina pathology.